Assessing the impact of the new context on economic development in Vietnam from 2011 to 2024 - Anh, Le Thi Tram; Anh, To Thi Van (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the influence of internal and external factors on Vietnam’s economic growth during a period shaped by digitalization, global integration via free trade agreements (FTAs), and climate change challenges. Utilizing a Vector Autoregression (VAR) model, the research analyzes key variables including skilled labor, internet access, patents, IT expenditure, climate costs, the KOF Globalization Index, balance of trade, and FTAs. The study covers a transformative phase of Vietnam’s economy, focusing on quantitative data to assess dynamic relationships. Skilled labor and internet access significantly boost economic growth, though the benefits of the internet exhibit a lag. Climate costs pose a substantial barrier to progress. Globalization drives short-term growth but introduces long-term risks, while FTAs show minimal direct impact on economic performance. The study underscores the importance of addressing internal strengths like education and digital infrastructure alongside external pressures like climate change and globalization. Limitations include reliance on estimated data for recent years, the VAR model’s linearity, and the omission of qualitative factors, suggesting future research directions. Policymakers should prioritize investments in education, digital infrastructure, innovation, and climate resilience while fostering balanced global integration to ensure sustainable economic growth for Vietnam.